2011
DOI: 10.1007/s11060-011-0737-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of 2-hydroxyglutarate and other metabolites in IDH1 mutant glioma patients using magnetic resonance spectroscopy

Abstract: Mutations of the isocitrate dehydrogenase 1 and 2 genes (IDH1 and IDH2) are commonly found in primary brain cancers. We previously reported that a novel enzymatic activity of these mutations results in the production of the putative oncometabolite, R(–)-2-hydroxyglutarate (2-HG). Here we investigated the ability of magnetic resonance spectroscopy (MRS) to detect 2-HG production in order to non-invasively identify patients with IDH1 mutant brain tumors. Patients with intrinsic glial brain tumors (n = 27) underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
243
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(262 citation statements)
references
References 29 publications
(41 reference statements)
15
243
2
2
Order By: Relevance
“…They found that 6 of the 13 genes with increased expression in ADC tumours were isoforms of collagen-binding proteins. 35 In order to confirm this result, the authors performed immunohistochemistry in both high-and low-ADC tumours to compare the expression of decorin and collagen one, three and six isoforms. There was no significant correlation between ADC values and collagen immunoreactivity scores.…”
Section: Study Validationmentioning
confidence: 90%
See 2 more Smart Citations
“…They found that 6 of the 13 genes with increased expression in ADC tumours were isoforms of collagen-binding proteins. 35 In order to confirm this result, the authors performed immunohistochemistry in both high-and low-ADC tumours to compare the expression of decorin and collagen one, three and six isoforms. There was no significant correlation between ADC values and collagen immunoreactivity scores.…”
Section: Study Validationmentioning
confidence: 90%
“…8 studies used data from The Cancer Genome Atlas (TCGA) and/or The Cancer Imaging Archive (TCIA); 1,16,23,27,32,34,38,41 2 studies were multi-institutional; 9,19 and the remaining 17 studies used local institutional data. 15,17,18,[20][21][22][24][25][26]28,30,31,33,[35][36][37]39,40 26 out of 27 studies were retrospective in design. The number of patients ranged from 10 to 104 patients, with a median of 38 patients.…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Although the concentration of 2-hydroxyglutarate in serum cannot be used to judge the status of IDH1 mutations, these mutations are associated with the accumulation of R(-)-2-hydroxyglutarate within the tumor. 12,13 Pope et al 14 suggested that MR spectroscopy could detect 2-hy-droxyglutarate in patients with IDH1-mutant glioma and provide a noninvasive measurement of 2-hydroxyglutarate in gliomas. However, the measurement of 2-hydroxyglutarate through MR spectroscopy is performed by special software and is inconvenient for clinical application.…”
mentioning
confidence: 99%
“…Preoperative precise detection of 2-hydroxyglutarate by MR spectroscopy is still under investigation. 7,9,17,26 Our study, which is based on microfluidics and use of specific antibodies for IDH1-mutant protein, was also applicable for detection of IDH1 mutation status.…”
Section: Feasibility Of Microfluidicsmentioning
confidence: 99%